Cochlear Ossification in a Patient with Cogan’s Syndrome Undergoing Bilateral Cochlear Implantation - Adam M. Cassis (Case Reports in Otolaryngology)
We present the case of a young female patient diagnosed with Cogan’s syndrome after the rapid onset of profond hearing and vestibular loss with concomitant eye symptoms. After appropriate medical treatment, her hearing did not respond and she underwent bilateral simultaneous cochlear implantation with findings of extensive cochlear ossification in both ears. The case and outcome are described in the body of the paper.